Cryopreserved Plasmodium vivax and cord blood reticulocytes can be used for invasion and short term culture - Borlon, C; Russell, B; Sriprawat, K; Suwanarusk, R; Erhart, A; Renia, L; Nosten, F; D'Alessandro, U (Elsevier, 2012)
The establishment of a Plasmodium vivax in vitro culture system is critical for the development of new vaccine, drugs and diagnostic tests. Although short-term cultures have been successfully set up, their reproducibility in laboratories without direct access to P. vivax-infected patients has been limited by the need for fresh parasite isolates. We explored the possibility of using parasite isolates and reticulocytes, both cryopreserved, to perform invasion and initiate short-term culture. Invasion results obtained with both cryopreserved isolates and reticulocytes were similar to those obtained with fresh samples. This method should be easily replicated in laboratories outside endemic areas and will substantially contribute to the development of a continuous P. vivax culture. In addition, this model could be used for testing vaccine candidates as well as for studying invasion-specific molecular mechanisms. © 2012 Australian Society for Parasitology Inc.